Anatomical Variation of Colon Detected on Abdominal Computed Tomography Correlated with Gender - Sharma, Prakash; KC, Subash; Gyawali, Merina; Lalchan, Subita; Poudel, Aseem (Nepalese Journal of Radiology, 2022)
Introduction: Anatomical variation of the colon can cause diagnostic dilemmas and pose a problem while radiological interpretation and during various procedures. Radiologists and clinicians should exert much caution during the procedures in such patients. This study was done to study the anatomical variation of the colon in abdominal CT scans and correlated the variations with gender. Methods: It was a cross-sectional study done at the Department of Radiology and Imaging of Manipal Teaching Hospital from September 2020 to March 2021. Abdominal CT was obtained and colonic position was evaluated. The Chi-square test was applied to assess the correlation between colonic variations and gender. Results: There were 388 patients in total. The age of the patients ranged from 3 years to 94 years. The mean age of the patients was 44.8±18.6 years. There were 166 (42.8%) females and 222 (57.2 %) males. Out of 388 patients, 170(43.8) had some colonic anatomical variations. Sixteen (4.1%) patients had retro gastric colon. Around 6% had a right retrorenal colon and 30(7.7%) had a left retrorenal colon. Seven (1.8%) patients had anterolateral hepatodiaphragmatic interposition. Forty-two patients (10.8%) had high positioned caecum. The redundant sigmoid colon was present in 38(9.8%) patients. There was no significant correlation between the colonic variation and gender. Conclusion: Different variations in the colon exist even in the Nepalese population, of which the radiologists, as well as the surgeons, should be aware.